Les acquis de la formation doctorale: perceptions des compétences développées - Bangali, Marcelline (Canadian Journal of Higher Education, 2021)
A number of studies point to particular challenges that some PhD graduates face in the labour market outside of academia. One of the main reasons for these difficulties is said to be a lack of knowledge or inadequacy of what doctoral graduates have acquired in terms of the skills sought by employers. However, apart from statistical data, there is little work that tells us about the perceptions that the various groups and individuals involved have of these skills. This article makes a contribution in this direction. It is based on the results of a sequential mixed methods study. The first stage consisted of a qualitative study using semi-structured interviews of 85 employed PhD graduates and 21 organizational leaders. The results of this study, whose data were processed using the Alceste method, were used to design a 45-item scale on the skills of doctoral graduates. This scale was measured in two questionnaire surveys completed by 2,139 employed doctoral graduates and 215 organizational leaders. Descriptive analyses comparing standardized averages (Cohen’s d) highlight points of convergence that show that doctoral training could be an asset for the development of future skills, especially those that are difficult to automate: complexity management, creativity, critical thinking.